Does Providing Care for Uninsured Patients Decrease Emergency Room Visits and Hospitalizations? - Ted MacKinney; Alexis M. Visotcky; Sergey Tarima; Jeff Whittle (SAGE Publishing, 2013)
Background: Access to primary care could reduce use of more costly health care by uninsured individuals through prevention and early treatment. We analyzed data from a program providing free primary care to test this hypothesis. Methods: We compared emergency room (ER) visits and hospitalizations among uninsured, low-income adults who received immediate versus delayed access to a program providing free primary care, including labs, X-rays, and specialty consultation. We used surveys to identify ER visits and hospitalizations during the 12 months preceding and following program enrollment or wait list entry. Results: Hospitalizations decreased from the year before entry to the year following entry in participants with immediate and delayed (6.0% vs 8.8% decrease) access. ER use also decreased in both groups (11.2% vs 15.4%). Conclusions: Free primary care services and specialty consultation did not reduce use of more costly health care services during its first year. More prolonged availability of primary care might have greater impact.